Disaggregating dismemberment: nullity, natality, and the hollowing of constitutional renewal in designed written constitutionalism - Kuo, Ming-Sung (Revista de Investigações Constitucionais, 2020)
This paper aims to rethink the idea of constitutional renewal through a dissection of Richard Albert’s ground-breaking concept of constitutional dismemberment. It is contended that under the rubric of constitutional dismemberment are two exceptional constitutional phenomena: the ought-to-be declared nullity of unconstitutional constitutional amendments and the legal unity-defying, extraconstitutional expression of what Hannah Arendt called “natality” in political action. The thesis is that attempts to tame revolutionary constitutional alteration with designed rules as to formal constitutional change as Albert’s illustrates are missing the meaning of constitution-making for a natality-driven constitutional renewal characteristically defies designed constitutional form. The concept of constitutional dismemberment is first dissected in light of Arendt’s idea of natality. With constitutional dismemberment unpacked, it is further observed that the constitution-making transmutes into the formal pronouncement of a new codified constitution in Albert’s rigid tripartite classification of constitutional changes into amendment, dismemberment, and enactment. Albert therefore inadvertently reduces constitution-making to the formal enactment of a new codified constitution with constitutional natality dismembered and constitutional renewal hollowed out. It is concluded that Albert’s formalistic conceptual framework of constitutional change reflects the centrality of comparative written constitutions in the place of comparative constitutional phenomena in current comparative constitutional studies.